IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL TO IMPROVE CREATIVE THINKING ABILITY - Dwi Tursina Utari; Rr. Indah Mustikawati (Universitas Negeri Yogyakarta, 2017)
This research is Classroom Action Research (CAR). The research aims to improve the Creative Thinking Ability of students class XI Accounting 2 in taxation subject at SMK Negeri 1 Yogyakarta academic year 2016/2017 by implementation of Problem Based Learning Model. The research conducted in two cycle. Each cycle consisted of four stages: planning stage, implementation stage, observation stage, and reflection stage. The technique applied for collecting data was observation, test, and documentation. The results: (1) According to the observation result and the Creative Thinking Ability post-test result from the cycle I at the amount of 52,01 increased to be 76,43 after the action in the cycle II. (2) According to the amount of students’ percentage who achieved the successful action, there is an increase for amount 65,32% from 9,68% in the cycle I to 75% in cycle II.Keywords: Problem Based Learning Model, Creative Thinking Ability of Student